Are changes in heart rate and/or arborisation of vaginal mucus useful parameters for detecting heat in heifers? - Norman, Frida (2008)
The milk production per cow has increased considerably during the last 50 years and due to the breeding for higher milk production also brings decreased reproduction efficiency. In a Swedish study 1996 it was shown that on average only half of all estruses were detected. Every time a farmer fails to detect oestrus it costs the farmer about 1200 Swedish crones and the need of means of detecting oestrus is therofore large. With this study we wanted to investigate if heart rate respectively crystallisation of vaginal mucus (arborisation) could be useful means of detecting oestrus. We monitored two oestrus cycles in four heifers. We found that during standing heat 81 % of the smears were 80-100 % covered with crystals while no smears during the luteal phase had this much crystals. During the luteal phase 74 % of the smears were 0-20 % covered with crystals. Five different kinds of crystals were observed in the smears, but they all appeared at all stages of the oestrus cycle. We also found that the heart rate were significant higher during the first oestrus than during the first luteal phase. In contrary to the first oestrus cycle the heart rate were significantly lower during the second oestrus compared to the second luteal phase. Possible reasons for these diverse results could be that the first oestrus was induced by prostaglandin and the fact that the heifers only had been in their new environment for less than two weeks before the first oestrus. The conclusions were that arborisation of vaginal mucus could be a useful mean of detecting oestrus in specific cases. Although an objective assessment of the crystals would be of interest in the future. According to the results of this study the heart rate is not a good parameter for detecting heat.